Effect of Roller Path on the Formability of Drawing Spinning - Han, Z.R.; Jia, Z.; Xiao, Y.; Liu, B.M.; Fan, Z.J. (Manufacturing Technology Journal, 2017)
Drawing spinning is widely used for the manufacture of cylinder parts from disk blank. And the roller path can affect its formability strongly. But how does the effect mechanism work is rarely revealed. The plastic of the metal is one key factor for the failure of spinning such as fracture and wrinkling. In order to reveal the relationship between the roller path and the formability, two working conditions with one-pass (Scheme I) and multi-pass (Scheme II) roller path are proposed. And the comparative analysis of their metal flow evolution is carried out by the finite element method. It is found that one-pass roller path isn't conducive to putting down the flange gradually. And this will bring larger deformation resistance to cause cylinder wall fracture and reduce the formability of drawing spinning.
Keywords: Multi-pass roller path; Drawing spinning; Formability; FEM